Knowledge of HIV/AIDS and the clinical and sexual practices of dental students - Aguiar, Vanessa Benigno Mota; Barros, Sérgio Lobão Veras; Sousa, Karinna Alves Amorim; Rego, Jessyara Brian dos Santos; Silva, Nádia Maria Pires; Araújo, Telma Maria Evangelista; Barros, Simone Souza Lobão Veras (Revista da ABENO, 2022)
The aim of the study was to assess knowledge of HIV/AIDS and the clinical and sexual practices of dental students. This was a cross-sectional study in which a self-administered questionnaire about age, gender, and dental program term; knowledge of HIV/AIDS transmission and prevention; use of personal protective equipment; prevention and occurrence of accidental exposure to biological material; post-exposure conduct; and sexual behavior was answered by dental students (n = 148, answer rate of 91.9%). Descriptive and inferential statistical analyses (chi-square and Fisher’s exact tests) were performed, at a significance level of 5%. Students correctly recognized the routes of HIV transmission, including “blood” (100%), “sexual.3%). Regarding frequency of condom use during sexual intercourse, 37% of dental students said “always,” 55.5% “sometimes” and 7.6% “never”. Regarding clinical practices, 99.3% of dental students said they used personal protective equipment, 28.4% had intercourse” (99.3%), “vertical transmission” (58.1%) and “sharing contaminated material” (94.6%), and ways of prevention, including “condom use” (100%) and “not sharing needles and syringes” (99suffered percutaneous injuries, the needle was the most cited exposure agent (32.5%) and in most cases (54.8%), no providences were taken after the accident. In conclusion, the students had good knowledge of HIV / AIDS and appropriate preventive attitudes in clinical care and handling of sharp instruments; however, they still need to be motivated with regard to condom use and oriented about care after accidental exposure to biological material.